2001
DOI: 10.1210/jcem.86.8.7773
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GH and/or Sex Steroid Administration on Abdominal Subcutaneous and Visceral Fat in Healthy Aged Women and Men

Abstract: Aging is associated with reduced GH, IGF-I, and sex steroid axis activity and with increased abdominal fat. We employed a randomized, double-masked, placebo-controlled, noncross-over design to study the effects of 6 months of administration of GH alone (20 microg/kg BW), sex hormone alone (hormone replacement therapy in women, testosterone enanthate in men), or GH + sex hormone on total abdominal area, abdominal sc fat, and visceral fat in 110 healthy women (n = 46) and men (n = 64), 65-88 yr old (mean, 72 yr)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(21 citation statements)
references
References 34 publications
4
15
0
1
Order By: Relevance
“…2 kg, and one reported carpaltunnel syndrome. Such adverse events are consistent with an increase in total body water associated with elevated GH concentrations, as also observed during GH administration (16,17). Clinical cardiac function and fasting glucose concentrations did not change.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…2 kg, and one reported carpaltunnel syndrome. Such adverse events are consistent with an increase in total body water associated with elevated GH concentrations, as also observed during GH administration (16,17). Clinical cardiac function and fasting glucose concentrations did not change.…”
Section: Discussionsupporting
confidence: 83%
“…However, only one of these interventions altered body composition significantly (15). In contrast, GH supplementation consistently decreases intraabdominal fat and increases lean body mass in GHdeficient adults (16,17). Whether an inadequate dose and/or frequency of secretagogue administration accounts for the lack of whole-body effects in earlier regimens is not known.…”
Section: Introductionmentioning
confidence: 99%
“…The significant impact of CAG n on (SAT thigh and SAT lower trunk ) and lacking impact on deeper adipose tissues (IMAT thigh and VAT) are interesting findings: they may indicate that actions of androgens on male adipose tissues are mainly associated with favorable impacts on subcutaneous compartments. This is in accordance with interventional studies of testosterone replacement therapy, in which subcutaneous compartments diminished (32,33), while only one small, older study reported diminished amounts of VAT (34). The interpretation of cross-sectional data is uncertain, but our study strongly indicates that VAT increases considerably from age 20 to 29 years, and that, on average, VAT is further increased in middle-aged men (21).…”
Section: Relative Thigh Satsupporting
confidence: 87%
“…31 More detailed analyses of regional adipose tissue distribution have yielded conflicting reports of the effects of androgens. Older eugonadal (baseline serum testosterone 15.3 nM) men with a mean BMI 26 kg/m 2 treated with intramuscular testosterone for 6 months had a non-significant 10% decrease in subcutaneous abdominal fat area, with no change in visceral or total intraabdominal fat (at the level of L4-L5 on MRI); 56 Body composition, metabolic syndrome and testosterone in ageing men CA Allan et al similarly, transdermal testosterone administered for 24 months to men with median BMI 28 kg/m 2 did not decrease visceral fat on CT examination. 57 Studies of 17-alkylated androgens (oxymetholone and oxandrolone) have shown both preferential loss of truncal FM 34 and an equivalent loss in both the trunk and the appendices.…”
Section: Testosterone and Body Compositionmentioning
confidence: 98%